Key technologies and application of optical transport network for leased line services - Xiongyan TANG; Haijun WANG; Hongbo YANG (Dianxin kexue)
The rapid development of leased line services has transformed the optical transport network from operator's basic network to leased line service network.With the withdrawal of MSTP,OTN has become the main network technology for high-value leased lines.Several key technical solutions and evolution of OTN carrying leased line were analyzed and researched.The problem of cascade protection in multi-domain OTN was researched.Interoperability of different venders’ equipment was researched and solved.SDN and OTN were proposed as the development direction for high-quality leased lines.ACTN-based SD-OTN controller northbound interface standard and YANG model,technical requirements of management and control for access OTN equipment were promoted in IETF and CCSA separately,which would promote decoupling of OTN network.China Unicom’s leading experience of development and deployment of SDN orchestrator on OTN for high quality leased line was shared.